Rare Dual Congenital Anomalies : Bronchogenic Cyst and Atrial Septal Defect - Gohil, Anjani; Bhende, Vishal; Lakhani, Gaurav (Journal of Neonatal Surgery, 2025)
We report an extremely rare case of a Bronchogenic Cyst incidentally identified via contrast enhanced computed tomography in a one and half-month-old male infant, a known case of Ostium Secundum Atrial Septal Defect and mild pulmonary hypertension. The patient was evaluated in detail and cystic mass resembling a Bronchogenic Cyst was found over lower paratracheal mediastinal space. The patient was planned for excision of the posterior mediastinal lesion using a right limited postero-lateral thoracotomy incision and complete excision was done and the mass was pathologically confirmed to be a Bronchogenic Cyst. This case is one of the few rare cases of infants with acyanotic congenital heart defect that were incidentally found to have a Bronchogenic Cyst. This case to our knowledge is one of the youngest patients yet and also highlights the importance of identifying rare causes like these amongst differentials of cough and wheeze responding poorly to regular treatment.